2022
DOI: 10.3389/fmolb.2022.887564
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the Essential Transcription Factor HP1043 of Helicobacter pylori: A Drug Repositioning Study

Abstract: Antibiotic-resistant bacterial pathogens are a very challenging problem nowadays. Helicobacter pylori is one of the most widespread and successful human pathogens since it colonizes half of the world population causing chronic and atrophic gastritis, peptic ulcer, mucosa-associated lymphoid tissue-lymphoma, and even gastric adenocarcinoma. Moreover, it displays resistance to numerous antibiotics. One of the H. pylori pivotal transcription factors, HP1043, plays a fundamental role in regulating essential cellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Accordingly, increasing efforts have been put forward in searching for new compounds able to inhibit the growth of pathogens by acting specifically on new molecular targets for novel drug discovery. As a result, many transcriptional regulators have been considered and studied as valid drug targets with promising results, including the H. pylori HP1043 regulatory protein [185,186]. Furthermore, the two-component systems (TCS) have received increasing attention [187].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, increasing efforts have been put forward in searching for new compounds able to inhibit the growth of pathogens by acting specifically on new molecular targets for novel drug discovery. As a result, many transcriptional regulators have been considered and studied as valid drug targets with promising results, including the H. pylori HP1043 regulatory protein [185,186]. Furthermore, the two-component systems (TCS) have received increasing attention [187].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in vivo and in vitro anti-tumor and growth suppression effects of ivermectin were demonstrated on GC, showing that ivermectin suppressed MKN1 cells growth through yes-associated protein 1 (YAP1) downregulation ( Nambara et al, 2017 ). To identify drugs capable of inhibiting the DNA-binding activity of the helicobacter pylori transcription factor HP104, a combination of computational and in vitro methods led to the discovery of three promising drugs, including temoporfin, trientine, and tetraethylenepentamine, for potential antibacterial applications ( Antoniciello et al, 2022 ). Table 4 provides a summary of available repurposed drugs in GC.…”
Section: Repurposed Drugs For Gastrointestinal Cancers Treatmentmentioning
confidence: 99%
“…To date, some investigations have been carried out in order to validate HsrA and ArsR as effective therapeutic targets against H. pylori infection as well as discovering low-molecular weight inhibitors of these RRs exhibiting strong bactericidal activities against antibiotic-resistant strains of this pathogen ( González et al., 2019a ; González et al., 2019b ; González et al., 2020 ; Antoniciello et al., 2022 ; González et al., 2022 ). Notably, some of the novel antibacterial candidates evaluated in these studies, including natural flavonoids and 1,4-dihydropiridines, have shown in vitro antimicrobial activities in the range of those observed with first-line conventional antibiotics ( González et al., 2021 ; González et al., 2022 ).…”
Section: Tcrs As Targets For Novel Antimicrobials Against H...mentioning
confidence: 99%